2017
DOI: 10.1016/j.apjtm.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNFA (−308G/A), IFNG (+874 A/T) and IL-10 (−819 C/T) polymorphisms with protection and susceptibility to dengue in Brazilian population

Abstract: This research identifies the association of the IFNG (+874 A/T), TNFA (-308G/A), IL-10 (-819 C/T) genotypes as a factor for protection, susceptibility and severity to dengue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
13
2
Order By: Relevance
“… 19 , 20 , 21 Thus the high levels of IL-10 in infected individuals could have been a result of the infection rather than the cause of infection. However, there are previous reports that high levels of IL-10 predispose to reinfection 8 , 9 , 10 and we found that no individuals with the IL-10 TT genotype (which was also associated with lower IL-10 levels) were infected. Taken together, these observations support the hypothesis that the association between IL-10 levels and schistosomiasis in our study is due to higher IL-10 levels predisposing to infection and lower levels conferring protection.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“… 19 , 20 , 21 Thus the high levels of IL-10 in infected individuals could have been a result of the infection rather than the cause of infection. However, there are previous reports that high levels of IL-10 predispose to reinfection 8 , 9 , 10 and we found that no individuals with the IL-10 TT genotype (which was also associated with lower IL-10 levels) were infected. Taken together, these observations support the hypothesis that the association between IL-10 levels and schistosomiasis in our study is due to higher IL-10 levels predisposing to infection and lower levels conferring protection.…”
Section: Discussioncontrasting
confidence: 59%
“…Tumour necrosis factor (TFN)-α and interleukin (IL)-10 have been associated with susceptibility and other key immune responses in many diseases including those caused by helminthes. 8 , 9 , 10 We therefore assessed cytokine levels as well as cytokine genotypes in preschool children at risk of schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents the characteristics of the nine included studies, along with their genotype and allele frequency distribution of TNF-α -308 G>A and TNF-α -238 G>A gene polymorphisms. Two studies each were from Brazil [ 27 , 31 ] and Mexico [ 26 , 32 ], while one study each from Cuba [ 25 ], India [ 28 ], Malaysia [ 30 ] and Sri Lanka [ 29 ]. Study samples varied from 43 cases [ 25 ] to 196 [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results were contradicted in another work, where TNF-α at high and medium concentration inhibited DENV replication in human dendritic cells, a primary DENV target cells (cited in [40]). The promoter -308A allele has been related to enhanced TNF-α gene transcriptional activity [41], and different studies have associated it with diverse dengue phenotypes or failed to do so: protective against development of DHF/DSS in Malaysia [40]; not associated in Mexico [42]; dominant model marginally protective against DF in Brazil [43]; risk factor for DHF in Venezuela [44] and Cuba [45].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we applied population genetics-informed meta-analyses to evaluate the genetic risk/protection conferred by 10 SNPs across seven genes mostly associated with dengue in the literature (PLCE1, TNFA, DC-SIGN/CD209, OAS1, OAS3, FCGR2A/CD32 and MICB; Table 1). We surveyed the literature for case-control cohorts [25,26,27,29,30,35,36,38,40,42,43,44,48,49,53,54,55,56,57,58], took advantage of available datasets chip-genotyped ( [47,59]and Oliveira et al 2018), and added a few case-control cohorts of our own (mostly Cambodia, Vietnam and few Brazilian individuals).…”
Section: Introductionmentioning
confidence: 99%